Laudato Si - Holden, William N. (Worldviews, 2018)
This article examines the highly influential Papal encyclical Laudato Si issued by Pope Francis in June 2015. The scientific basis behind climate change is discussed, as are the consequences of climate change, which will be disproportionately borne by the poor countries and poor peoples of the world. The Pope’s prescriptions for coping with climate change are reviewed and the article concludes with a discussion of how Laudato Si exemplifies the simultaneous, and frequently intersecting, themes of protecting the environment and protecting the poor in Catholic social thought. In many ways, Laudato Si is the product of the church of the poor confronting climate change.